Adelobotrys tessmannii (Merianieae, Melastomataceae) and allies: a refined circumscription and description of two new Amazonian species with notes on their ecology - Schulman, Leif Edvard; Ruokolainen, Kalle (Phytotaxa, 2015)
Adelobotrys tessmannii is re-circumscribed and a lectotype is designated. Two new species, A. latifolius and A. microcarpus, are described, and all three species are illustrated. They have a Western Amazonian, broadly sympatric distribution, which is depicted. Field surveys and chemical soil analyses presented show that A. latifolius prefers more fertile soils than A. microcarpus¸ while A. tessmannii does not differ from the other species in this respect.